2023
DOI: 10.1088/0256-307x/40/11/118101
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Orientated Graphite Double-Layer Homo-Structure with Broadband Microwave Absorption

Jun-Song 俊松 Wang 王,
Wei 伟 Ding 丁,
Cheng-Hong 成宏 Zhang 张
et al.

Abstract: In this work, we utilized magnetic fields as an efficient tool to manipulate the orientation as well as the electromagnetic properties of graphite micro-flakes (GMFs) and first realized the GMFs double-layer homo-structure, which shows excellent EM absorption properties. With tuning the direction of a small magnetic field (850 Gs), vertical and horizontal aligned GMFs are produced. Their electromagnetic parameters are effectively tailored by this magneto-orientation effect and the vertical and horizontal align… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In our previous work, it was found that the validity of magnetocontrolling is not only related to B and ∇B, but also to the shape of the material itself [22,29]. In this work, we tried to explore the shape factor effect on the magneto-controlled motion in detail.…”
Section: The Effect Of the Shape Factor Of Materialsmentioning
confidence: 99%
“…In our previous work, it was found that the validity of magnetocontrolling is not only related to B and ∇B, but also to the shape of the material itself [22,29]. In this work, we tried to explore the shape factor effect on the magneto-controlled motion in detail.…”
Section: The Effect Of the Shape Factor Of Materialsmentioning
confidence: 99%